Funniest Thing I've Seen Since [href="http://flic.kr/p/KGEGB"]. Shifting Perspectives from Multimedia Artefacts to Utterances - Adams, Brett; Phung, D.; Venkatesh, S. (The Association for Computer Machinery (ACM), 2012)
With Multimedia Information Retrieval frustrated by the seemingly intractable semantic gap, we turn to the related field of linguistics for fresh inspiration and ideas for old problems and new opportunities. An explosion in the amount and ease with which multimedia items are created and shared, courtesy of new devices and Web 2.0, prompts us to consider what happens when those items are viewed not as artefacts, or "built things", but as utterances. These conversations occur in a mixture of mediums, including text, images, audio, and video, and channels, including Twitter, Facebook, Youtube and blogs, and range in scope from one-to-one exchanges to loosely-bounded meta-conversations that cross cultures and span the globe via remixing of shared meanings like memes. We propose that MIR add to its toolbox a linguistic perspective, and highlight three useful emphases of research: genre, emergence, and effect.